2022
DOI: 10.1002/bse.2987
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable management of electronic waste: Empirical evidences from a stakeholders' perspective

Abstract: With rapid advancements in technology, the evolution and demand for electronic/ electric devices have drastically increased. The exponential increase in the use of technology to fulfill the needs of the fast-paced information era has led to electronic and electrical devices being discarded or disposed of at a faster rate than in the past. This phenomenon has resulted in e-waste becoming the fastest-growing form of solid waste. E-waste is classified as hazardous waste and can be harmful to the environment and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 94 publications
0
14
0
1
Order By: Relevance
“…The following steps can be taken to avoid electronic waste that can be harmful to human health: (1) Prevent the generation of electronic pollutants at the source, identify what hazardous substances are in e-waste sources, their environmental behavior, and their public and ecological health risks, and identify environmentally friendly materials to replace those materials producing hazardous substances; (2) prevent electronic products from turning into electronic pollution by following an intermediate steps: enhance the recycling rate and its management mechanism, improve the life of electronic products, raise people's awareness of sustainability through education, and reduce the generation of electronic pollution; (3) develop a series of pollution treatment mechanisms after the generation of e-waste, such as effective e-waste disposal methods, ecologically responsible management, and routine monitoringv ( 13 , 41 43 ). Several methods have been built to manage e-waste, including life cycle assessment (LCA), material flow analysis (MFA), multi-criteria analysis (MCA), and extended producer responsibility (EPR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following steps can be taken to avoid electronic waste that can be harmful to human health: (1) Prevent the generation of electronic pollutants at the source, identify what hazardous substances are in e-waste sources, their environmental behavior, and their public and ecological health risks, and identify environmentally friendly materials to replace those materials producing hazardous substances; (2) prevent electronic products from turning into electronic pollution by following an intermediate steps: enhance the recycling rate and its management mechanism, improve the life of electronic products, raise people's awareness of sustainability through education, and reduce the generation of electronic pollution; (3) develop a series of pollution treatment mechanisms after the generation of e-waste, such as effective e-waste disposal methods, ecologically responsible management, and routine monitoringv ( 13 , 41 43 ). Several methods have been built to manage e-waste, including life cycle assessment (LCA), material flow analysis (MFA), multi-criteria analysis (MCA), and extended producer responsibility (EPR).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increase in the disposal of end-of-life (EoL) electrical and electronic goods, electrical and electronic waste (e-waste) contribute as one of the major pollution-causing products. Without proper management, the presence of heavy metals such as Hg, Cd, Pb, Co, Ni, Ti, Ag, Hg, Cd, As, and brominated flame retardants (BFRs), as well as other potentially dangerous compounds in e-waste, poses a threat to both the environment and human health ( 1 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The descriptors used were: (ALL ("circular economy" ) AND ( "Measurement" ) AND ( "Sustainable Development" ) AND ( "Analytical Hierarchy Process" ) ) AND ( ( ( circular AND economy ) ) AND ( measurement ) ) AND ( sustainable ) AND ( LIMIT-TO ( PUBYEAR , 2022 ) OR LIMIT-TO ( PUBYEAR , 2021 ) OR LIMIT-TO ( PUBYEAR , 2020 ) OR LIMIT-TO ( PUB-YEAR , 2019 ) OR LIMIT-TO ( PUBYEAR , 2018 ) ) AND ( LIM-IT-TO ( DOCTYPE , "ar" ) ). The state-of-the-art review revealed 148 possible articles, 28 of which were good matches for the subject and were used for the CE discussions since they addressed some of the CE steps, such as, for example, reduce, reuse, and recycle (Kumar et al, 2021;, or focused on energy and carbon emissions (Mishra et al, 2021); solar energy (Erol et al, 2021), biomass (Facchini et al, 2021), and e-waste (Alblooshi et al, 2022). However, most of these publications refer to the need to identify barriers to CE implementation (Kumar et al, 2021;Ullah et al, 2021;Irfan et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In these steps, the information about each decision-maker's opinion on the importance of the criteria and performance of the alternatives was collected. Using the scores assigned by the experts to each criterion and the SMART method, the subjective weights of the criteria were determined based on Equation (6). The scores and subjective weights are presented in Table 3.…”
Section: An Empirical Studymentioning
confidence: 99%
“…The rise in sales of e-products makes the management of e-wastes more challenging for societies and governments [6]. Many industrialized and developed countries have established their e-waste management systems, but less industrialized and developing countries have several issues due to lack of proper waste management infrastructure [7].…”
Section: Introductionmentioning
confidence: 99%